The Effectiveness of Leaflets and Posters as a Health Education Method - Hasanica, Nino (Mater Sociomed, 2020)
INTRODUCTION: Health education is a process of acquiring knowledge and skills in order to improve the health of the individual and the community. It is considered the most effective, most economical and most rational aspect of health care and health culture. AIM: To provide data on the effectiveness of printed health-educational materials. METHODS: This is a quantitative, applied, descriptive-analytical study. According to the type of research, it presents a public health evaluation manipulative study with triple testing. The research was conducted in elementary schools in the Zenica-Doboj Canton. The total number of students participating in the research is divided into groups: examined, control group. The research consisted of four phases. The research tool is a modified questionnaire The Health Behavior in School-aged Children (HBSC) with 38 questions, 8 modules. RESULTS: The total number of respondents was 120. The method of distribution of health-educational posters shows a lower but still present statistical significance (p<0.05) in relation to the acquired knowledge and a change in attitudes between the conducted surveys at different time points. There is no statistically significant change (p>0.05) in the level of knowledge and attitudes using leaflets between conducted surveys at three different times. In the control group without education, there was a low statistical significance (p<0.05) in terms of changing the level of knowledge and attitudes. CONCLUSION: The distribution of health-educational posters is recommended in situations where it is necessary to reach a wide audience for a long period of time, if the site of the poster is protected. According to this study, there is no evidence that the leaflet distribution method should be used when it comes to the promotion of healthy lifestyles among healthy children. Alternative methods and ways of health education need to be identified.